2019
DOI: 10.1001/jamasurg.2018.3180
|View full text |Cite
|
Sign up to set email alerts
|

Biliary-Enteric Drainage vs Primary Liver Transplant as Initial Treatment for Children With Biliary Atresia

Abstract: Patients who underwent pLT experienced superior long-term survival compared with patients who underwent BED treatment. Multi-institutional trials are needed to determine which initial treatment is most advantageous to patients with biliary atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 23 publications
(51 reference statements)
0
29
0
Order By: Relevance
“…43 They found that patients that underwent primary liver transplantation had significantly lower long-term mortality risk than those that underwent Kasai procedure followed by a salvage liver transplant (HR 0.19 vs 0.43). 43 Unfortunately, the study suffers from a number of limitations the most important of which is selection bias as it is unknown why the patients that underwent a primary liver transplant were not treated first with a Kasai portoenterostomy. Though the median age at which salvage and primary liver transplant performed was approximately equal (315 vs 313 days of age), performing a primary liver transplant in all patients with biliary atresia without primary biliary drainage would have an unknown effect on the age at which these patients would require liver transplantation and condemn approximately 30% of this patient population to lifelong immunosuppression not to mention a significantly more dangerous and technically challenging procedure.…”
Section: Changing Landscape and The Role Of Transplant In Bamentioning
confidence: 98%
See 2 more Smart Citations
“…43 They found that patients that underwent primary liver transplantation had significantly lower long-term mortality risk than those that underwent Kasai procedure followed by a salvage liver transplant (HR 0.19 vs 0.43). 43 Unfortunately, the study suffers from a number of limitations the most important of which is selection bias as it is unknown why the patients that underwent a primary liver transplant were not treated first with a Kasai portoenterostomy. Though the median age at which salvage and primary liver transplant performed was approximately equal (315 vs 313 days of age), performing a primary liver transplant in all patients with biliary atresia without primary biliary drainage would have an unknown effect on the age at which these patients would require liver transplantation and condemn approximately 30% of this patient population to lifelong immunosuppression not to mention a significantly more dangerous and technically challenging procedure.…”
Section: Changing Landscape and The Role Of Transplant In Bamentioning
confidence: 98%
“…Though this has been the standard of care, a recent study in JAMA surgery has challenged this paradigm to suggest that all biliary atresia patients should undergo a primary liver transplant. 43 The authors performed a retrospective administrative database review of 626 patients that either underwent a primary liver transplant (n=351) or a Kasai procedure (n=351). 43 They found that patients that underwent primary liver transplantation had significantly lower long-term mortality risk than those that underwent Kasai procedure followed by a salvage liver transplant (HR 0.19 vs 0.43).…”
Section: Changing Landscape and The Role Of Transplant In Bamentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, today, a strategy consisting in sequential KP followed by LT if required still constitutes the preferred scenario in most centers, particularly because KP allows 14-44% of BA patients to escape LT until adulthood (12)(13)(14)(15)(16)(17). Paradoxically, only few studies have tried to systematically investigate whether LT outcomes are actually impacted by a previous KP, providing contradictory conclusions (18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The article from LeeVan et al, entitled “Biliary‐enteric drainage vs primary liver transplant as initial treatment for children with biliary atresia,” is a retrospective cohort study that examines long‐term outcomes for children with biliary atresia (BA) through analysis of information obtained from the California Office of Statewide Health Planning and Development (OSHPD), an administrative database. Specifically, the researchers compare outcomes between a cohort of BA patients who underwent a biliary enteric drainage (BED) procedure (presumably a Kasai hepatoportoenterostomy) as the primary therapy to those who underwent a primary liver transplant (pLT) without a previous BED.…”
mentioning
confidence: 99%